2016
DOI: 10.1016/j.jneb.2016.07.002
|View full text |Cite
|
Sign up to set email alerts
|

Fruit and Vegetable, Fat, and Sugar-Sweetened Beverage Intake Among Low-Income Mothers Living in Neighborhoods With Supplemental Nutrition Assistance Program–Education

Abstract: Supplemental Nutrition Assistance Program-Education interventions are related to increased intake of FV and decreased consumption of high-fat foods and SSBs, but not overall diet quality. Future studies should include assessment of physical activity to investigate caloric balance in association with levels of SNAP-Ed interventions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 11 publications
(11 reference statements)
0
12
0
Order By: Relevance
“…In the state of Indiana, SNAP-Ed has been successful at reducing food insecurity in women and families [ 33 , 34 ]; this suggests that SNAP-Ed has the potential to improve diet and health as food insecurity has been directly linked with poor diet quality [ 35 ], and suboptimal biomarkers of nutrition status [ 36 , 37 ], and many chronic diseases [ 38 , 39 ]. Two recent studies in California suggested that SNAP-Ed programing is associated with increased fruit and vegetable intakes as larger gains were observed in areas with more SNAP-Ed reach [ 40 , 41 ]. However, in these reports, SNAP-Ed participation was not associated with any significant changes in overall diet quality [ 40 ], whereas a study in the U.S. Mountain region found that Expanded Food and Nutrition Education Program, another federally funded nutrition education program, is associated with improved overall diet quality [ 42 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the state of Indiana, SNAP-Ed has been successful at reducing food insecurity in women and families [ 33 , 34 ]; this suggests that SNAP-Ed has the potential to improve diet and health as food insecurity has been directly linked with poor diet quality [ 35 ], and suboptimal biomarkers of nutrition status [ 36 , 37 ], and many chronic diseases [ 38 , 39 ]. Two recent studies in California suggested that SNAP-Ed programing is associated with increased fruit and vegetable intakes as larger gains were observed in areas with more SNAP-Ed reach [ 40 , 41 ]. However, in these reports, SNAP-Ed participation was not associated with any significant changes in overall diet quality [ 40 ], whereas a study in the U.S. Mountain region found that Expanded Food and Nutrition Education Program, another federally funded nutrition education program, is associated with improved overall diet quality [ 42 ].…”
Section: Discussionmentioning
confidence: 99%
“…Two recent studies in California suggested that SNAP-Ed programing is associated with increased fruit and vegetable intakes as larger gains were observed in areas with more SNAP-Ed reach [ 40 , 41 ]. However, in these reports, SNAP-Ed participation was not associated with any significant changes in overall diet quality [ 40 ], whereas a study in the U.S. Mountain region found that Expanded Food and Nutrition Education Program, another federally funded nutrition education program, is associated with improved overall diet quality [ 42 ]. Therefore, rigorous evaluation of this program is warranted.…”
Section: Discussionmentioning
confidence: 99%
“…Another state compared dietary behaviors reported through its telephone survey of low-income moms in census tracts with high, moderate and low exposure to SNAP-Ed interventions. Higher program exposure was associated with lower reported consumption of sugar-sweetened beverages and high-fat foods and higher intake of fruits and vegetables [25].…”
Section: Overview Of the Snap-ed Evaluation Frameworkmentioning
confidence: 99%
“…Published evaluation studies of school-based SNAP-Ed interventions have been limited in number and largely qualitative, focusing on schools’ readiness and capacity to implement such programs ( Pope et al, 2020 , Lee et al, 2019 ). While interventions that focus on PSE changes are becoming more common ( Gleason et al, 2018 ), most studies have reported on the influence of direct education, and found limited impact on student weight status ( Molitor et al, 2016 , Long et al, 2013 , United States Department of Agriculture, Food and Nutrition Service, 2012 ). Further, the majority of these studies focus on nutrition-related interventions and outcomes; few studies aiming to increase student PA do not demonstrate increased PA and lack objective measures of student health or fitness ( Lee et al, 2019 , Cheng et al, 2015 , Bea et al, 2015 , Hecht et al, 2013 ).…”
Section: Introductionmentioning
confidence: 99%